Mapping the Student intra-departmental “mobility” on the Department of Philology at the University of Ioannina, Greece: A research approach - Fykaris, Ioannis; Siapkas, Konstantinos (International Research in Education, 2023)
This article refers to the intra-departmental development and mobility of the students, as a basis of reference the qualitative and quantitative characteristics of the students of the Department of Philology of the University of Ioannina in Greece, in relation to the possibilities given to them by the Department’s Study Program. The research presented in the relevant article is original and highlights data on the subject, which can strengthen reflection on the issue of student development during their studies. The research is based on the methodological principles of the case study, from which, however, useful conclusions can be drawn and give reasons for reflection on the quality course and upgrading of students in modern Higher Education, both in Greece and internationally.